Different Talks with Different Folks: A Comparative Survey of Stakeholder Dialog in Germany, Italy, and the U.S - Habisch, André 1963-; Patelli, Lorenzo; Pedrini, Matteo; Schwartz, Christoph (2011)
Although theoretical underpinnings of stakeholder dialog (SD) have been extensively discussed in the extant literature, there is a lack of empirical studies presenting evidence on the SD initiatives undertaken by firms. In this article, we provide information about 294 SD initiatives collected through a content analysis of the sustainability reports published by large firms in Germany, Italy, and the U.S. In addition to a country-based description of the different forms, stakeholder categories, and topics of the SD initiatives, we explore the relationship between SD and characteristics of national business systems. Overall, we find firms undertake few SD initiatives, using low-involvement forms of dialog, and focusing on one category of stakeholders per initiative. Results suggest that the explicit approach to corporate social responsibility (CSR) favors the quantity of SD initiatives, but neglects the importance of the level of involvement and diversity of stakeholders participating at the dialog. Finally, we find public policies on CSR have a substantial influence on SD in national business systems with an implicit approach to CSR. Public policies based on a shared discussion involving multiple social actors encourage SD initiatives that use different forms of dialog and are characterized by high level of involvement. Our findings offer contributions to the ongoing debate about the effectiveness of SD and its relationship with CSR.
Keywords: international study; Corporate Social Responsibility; Sustainability reporting; stakeholder dialog